2017
DOI: 10.1186/s40249-017-0257-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the prevalence of urogenital schistosomaisis and transmission risk factors amongst school-aged children around Mapé dam ecological suburbs in Malantouen district, Cameroon

Abstract: Background: Urogenital schistosomiasis is a parasitic infection of public health importance that affects over 112 million people worldwide. The study aimed at assessing the urogenital schistosomiasis prevalence and risk factors of transmission around Mape dam suburds in Malantouen district, West, Cameroon. Methods: The study was conducted using semi-structured pretested questionnaires to collect socio-demographic and ecological data. Urine samples were also collected and used to confirm the prevalence of schis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 22 publications
(71 reference statements)
9
16
1
Order By: Relevance
“…Even if serious pathology due to schistosomiasis has largely been overcome thanks to preventive chemotherapy, sub-Saharan Africa still includes large areas with high-intensity infection dynamics. Risk factors associated with urinary schistosomiasis in school children, investigated in Cameroon [ 19 ] and in Zambia [ 20 ] demonstrate that local transmission is strongly associated with gender and age with the highest intensity of infection in 10–15 years olds corroborating what is reported in other parts of Africa, e.g., by Tingley et al [ 21 ]. Interestingly, Stensgaard et al [ 22 ] found intensity of infection to be slightly more pronounced at higher altitudes, which goes against the belief that low night-time temperatures inhibit transmission by affecting snail reproduction negatively.…”
Section: All Together Nowsupporting
confidence: 73%
“…Even if serious pathology due to schistosomiasis has largely been overcome thanks to preventive chemotherapy, sub-Saharan Africa still includes large areas with high-intensity infection dynamics. Risk factors associated with urinary schistosomiasis in school children, investigated in Cameroon [ 19 ] and in Zambia [ 20 ] demonstrate that local transmission is strongly associated with gender and age with the highest intensity of infection in 10–15 years olds corroborating what is reported in other parts of Africa, e.g., by Tingley et al [ 21 ]. Interestingly, Stensgaard et al [ 22 ] found intensity of infection to be slightly more pronounced at higher altitudes, which goes against the belief that low night-time temperatures inhibit transmission by affecting snail reproduction negatively.…”
Section: All Together Nowsupporting
confidence: 73%
“…There is limited discussion of the role of gender in neglected tropical disease (NTD) programmes, despite known gender-specific differences in terms of prevalence [1][2][3], transmission and exposure to NTDs [4]. These differences have been attributed to biological vulnerability and gender roles [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Annual mass drug administration (MDA) of praziquantel to schoolchildren in endemic areas represents the country primary control strategy against the disease ( 2 ). The country is home to S. mansoni ( 3 7 ) and S. haematobium ( 1 , 3 , 4 , 8 ) causing the hepatointestinal and urogenital forms of the disease respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The mapping of the disease prevalence and associated burden has reliably guided anti-schistosomiasis intervention strategies during the control phase of the national anti-schistosomiasis programs ( 13 15 ). Defining the prevalence of infection and disease and the biosocial factors that foster the infection and the disease have considerably helped MDA campaigns ( 1 , 2 , 5 8 , 13 , 14 ). At present, schistosomiasis elimination in endemic areas like Cameroon requires tractable approaches for the mapping of risks of prevalence and burden as this will considerably help ameliorate the current control strategies into elimination tools ( 9 , 11 , 12 , 14 , 16 ).…”
Section: Introductionmentioning
confidence: 99%